2016
DOI: 10.1590/1678-4324-2016160147
|View full text |Cite
|
Sign up to set email alerts
|

Histological Observation and Expression Patterns of antimicrobial peptides during Fungal Infection in Musca domestica (Diptera: Muscidae) Larvae

Abstract: Housefly, Musca domestica, has a complicated immune system. However, its underlying operating mechanism remains elusive. Candida albicans is a major pathogen affecting humans by causing deep infection fungous disease, but it is non-symbiotic in houseflies. To investigate the C. albicans infection process in housefly, the changes in morphological and histological and expression patterns of antimicrobial peptide were monitored to indicate the insect's response to fungal infection. The results showed that scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Also, increase in number of hemocytes was in Anopheles gambiae upon infection with Escherichia coli (King, 2013). These reports suggested that, insect hemocells were constantly regenerated and kept a dynamic change during insect infection (Jiangfan et al, 2016;Mishra et al, 2015). The hemocytes formed multicellular aggregates, i.e., nodules, at the first period post injection that aided to entrap the invading cancer cells.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Also, increase in number of hemocytes was in Anopheles gambiae upon infection with Escherichia coli (King, 2013). These reports suggested that, insect hemocells were constantly regenerated and kept a dynamic change during insect infection (Jiangfan et al, 2016;Mishra et al, 2015). The hemocytes formed multicellular aggregates, i.e., nodules, at the first period post injection that aided to entrap the invading cancer cells.…”
Section: Resultsmentioning
confidence: 96%
“…Knowledge on how the insect innate immune response to fight foreign body aided to understand the first step in human diseases interaction (Wang et al, 2013;Singh et al, 2014;Wu et al, 2014;Khalil et al, 2015). Injury, rolling and ingestion methods are techniques of insect infection that have been successfully established (Jiangfan et al, 2016). The injury method mainly used needles to deliver foreign bodies by piercing the somatic layer or directly injects foreign cell into the insect coelom to cause acute infection and rapidly activate immune response (Matsumoto et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AMP-17 (Musca domestica antimicrobial peptide-17) is encoded by a speci c high-expression gene selected from M. domestica transcriptome database constructed after microbial infection 12 hours. In the previous study, our research team successfully produced the recombinant protein AMP-17 with excellent antifungal activity in a prokaryotic expression system [14][15]. Further research has found that it can reduce the cell wall integrity of C. albicans, destroy the cell membrane structure, and increase cell membrane permeability [16].…”
Section: Introductionmentioning
confidence: 99%